Examining Incoming Credit Differences Between First-Year and Transfer Students - Yang, Yang; Briggs, Kelly; Avalos, Sandra; Anderson, Christina M. (My University, 2018)
In this study, the difference in the number of initial credits between incoming transfer and first-year students entering a land grant university in a professional education program was examined (N = 488). A multivariate analysis of variance revealed that transfer students transferred significantly more total credits and more credits that counted toward degree programs than did first-year students. Undergraduates who had graduated from small high schools transferred more credits and more credits that counted than did those from large high schools. However, first-year students transferred a significantly higher percentage of total credits that counted toward the degree programs than did transfer students. Implications for advisors, institutions, and policy makers are discussed.